ZEEHC: Zone-Based Energy Efficient Hierarchal Clustering Hierarchy for Wireless Sensor Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Sensor Network (WSN) is an emerging technology with potential applications in the field of habitat monitoring and industrial applications. Sensors monitor changes in an environment's physical attribute such as temperature, and observe the data collected and forward it to the base station (BS). Mostly these sensors are unattended, and their limited battery life makes energy a valuable resource that has to be used wisely. For the collection of information, the sensor network must be maintained for a longer duration of time in an energy-efficient manner.Therefore, designing protocols that prolong the life of the network and which are energy-efficient is incessantly fascinating. This paper proposed a protocol referred to as the zone-based energy-efficient hierarchical clustering (ZEEHC) protocol that divides the network into small zones and increases network lifetime. In order to achieve minimum energy consumption, multi-hop contact is implemented between ZHs - CHs -BS. The results further reveal that the proposed protocol significantly outperforms existing algorithms in terms of energy optimization and system lifetime.